2010
DOI: 10.1002/pits.20534
|View full text |Cite
|
Sign up to set email alerts
|

The differences between retained and promoted children in educational services received

Abstract: The purpose of this study was to determine whether students retained in first grade, relative to similarly low achieving students who were promoted, differed in the number of remedial educational services received by students in the year pre- retention year and in the repeat year. Study participants were 769 relatively low achieving first grade students, of whom 165 were retained in first grade and 604 were promoted. Controlling for students’ conditional probability of being retained, based on propensity score… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 23 publications
0
18
0
Order By: Relevance
“…Holmes' (1989) data, Peterson and Hughes (2011) found that both low-performing promoted and repeated elementary school students were actually given fewer support services than received in the preceding year.…”
Section: Current State Of Grade Repetition Literaturementioning
confidence: 99%
See 4 more Smart Citations
“…Holmes' (1989) data, Peterson and Hughes (2011) found that both low-performing promoted and repeated elementary school students were actually given fewer support services than received in the preceding year.…”
Section: Current State Of Grade Repetition Literaturementioning
confidence: 99%
“…The consequences of this decision are many; therefore, the social-emotional needs must not be overlooked when considering the effectiveness of this practice (Peterson & Hughes, 2011). Penna and Tallerico (2005) claimed that in order to attend to the social-emotional needs of repeated students the curriculum must be different.…”
Section: Social Promotionmentioning
confidence: 99%
See 3 more Smart Citations